Evaluation of the Effectiveness of Protective Patches on Acupoints to Preserve the Bioenergetic Status against Magnetic Fields. (17th September 2018) - Molinari, Claudio; Stoppa, Ian; Limardo, Nicola; Uberti, Francesca
Abstract : The potentially harmful nature of electromagnetic fields (EMF) and static magnetic fields (SMF) has become a major problem in recent years. All these elements could be combined to produce cellular responses. For example, the orientation of molecules of water or other complex molecules, growth and cell viability, cell morphology, and intracellular metabolic pathways have demonstrated binding to magnetic fields. The effect of EMF and SMF on humans is a topic of great importance, especially because modern technology has introduced artificial magnetic fields such as those generated by power lines, mobile communications, and medical imaging equipment. A relevant problem is certainly that of professional exposure. The aim of this study was the evaluation of the effectiveness of a commercially available device, Skudo® patches (Edil Natura S.r.l., Novara, Italy), in protecting magnetic resonance operators from the influence of magnetic fields such as those present in the workplace. Skudo® patches are designed to protect microareas of the body from external electromagnetic disturbances. In this study, 10 male Italian volunteers aged between 50 and 60 were enrolled in the hospital. All participants were subjected to measurements at 4 specific time points to evaluate the effectiveness of Skudo® to counteract both EMF and SMF magnetic fields by evaluating the level of bioenergetic reactivity. To perform the measurements, a variant of the Ryodoraku method has been used, based upon the assessment of electropermeability. In particular, 12 acupoints were measured, one for each of the main meridians. This study shows that both SMF and EMF cause an alteration of the body's water system. The application of Skudo® patches determines a regularization of bioenergetic levels related to the water system. The application of Skudo® on the EMF source has suppressed the imbalance effect of the water system found in the subject without any protection.